1991
DOI: 10.3109/00207459108985447
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields, brain and immunity: Effect on humoral and cell-mediated immune responses

Abstract: Magnetic fields (MF) can influence biological systems in a wide range of animal species and humans. We report here on the influence of static MF, locally applied to the brain area, on immune system performances in the rat. In the first series of experiments two AKMA micromagnets (M) with the influx density of 600 Gauss were bilaterally implanted (with "N" polarity facing the cranial bones) and fixed to the skull posterior to the fronto-parietal suture (parietal brain exposure). Rats implanted with iron beads (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 77 publications
0
9
0
1
Order By: Relevance
“…The area of infarct in the distal MCAo model exclusively affected the cortex, while the suture MCAo model affected both the cortex and striatum. Other studies have suggested that brain lesion sizes correlate with different immune responses (Jankovic et al, 1991, Kang et al, 1991, Kriegsfeld et al, 2003). Lymphocyte response may be dependent on where the infarct occurs.…”
Section: Discussionmentioning
confidence: 96%
“…The area of infarct in the distal MCAo model exclusively affected the cortex, while the suture MCAo model affected both the cortex and striatum. Other studies have suggested that brain lesion sizes correlate with different immune responses (Jankovic et al, 1991, Kang et al, 1991, Kriegsfeld et al, 2003). Lymphocyte response may be dependent on where the infarct occurs.…”
Section: Discussionmentioning
confidence: 96%
“…the immune response depending on the time of exposure Brief experimentally induced mental stress was shown to and the region of the brain exposed (22). Mice chronienhance blood natural killer (NK) cell mobilization and cally exposed to 50 Hz EMFs, in the same conditions as activity (7-10) and to reduce blood CD3+ lymphocytes humans, showed reduced total lymphocytes, leukocytes, (9-10).…”
mentioning
confidence: 98%
“…Tenforde and Shifrine (1984) examined the effects of long continuous magnetic field exposure (6 days at 1.5 T) on the immune system of mice, and no effects were detected. The elevated levels of several immune had been reproted at the various static magnetic field treatments (Jankovic et al, 1991(Jankovic et al, , 1993(Jankovic et al, , 1994. The lysozyme concentration in the Caspian kutum fry showed a decreasing trend during exposure to the SMFs at 2.5 to 7.5 mT.…”
Section: Discussionmentioning
confidence: 97%